Penegakan Hukum Terhadap Tindak Pidana Perjudian Ditinjau Berdasarkan Pasal 303 Kitab Undang-Undang Hukum Pidana - Raden Sumito Joyokusumo; Rina Arum Prastyanti; Muhammad Habib; Evi Elisanti (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
This study aims to determine 1) the law enforcement against gambling crimes as reviewed based on Article 303 of the Criminal Code. 2) the obstacles and challenges faced in law enforcement against gambling crimes as reviewed based on Article 303 of the Criminal Code. This research method uses an empirical juridical approach, which is research that examines legal realities that occur in society, by looking at it from an empirical perspective. The types of data used are primary data through interviews and secondary data sourced from primary, secondary, and tertiary legal materials. Data collection techniques are carried out through interviews and literature studies. Data analysis techniques are carried out descriptively qualitatively with data reduction, data presentation, and drawing conclusions. The results of the study indicate that law enforcement against gambling crimes as reviewed based on Article 303 of the Criminal Code based on law enforcement theory according to Soerjono Soekanto, the success of law enforcement is influenced by five factors: legal factors (legal substance), law enforcement factors, means or facilities factors, community factors, legal culture factors. Article 303 of the Criminal Code provides a clear legal basis for prosecuting perpetrators of gambling crimes, both as organizers and participants. Obstacles faced in law enforcement against offline gambling include proving the elements of the crime, limited human resources and infrastructure of law enforcement officers, and social and cultural factors, where gambling is still considered a tradition or social entertainment that is difficult to eradicate. Obstacles faced in law enforcement against online gambling include limited regulations in the Criminal Code, difficulties in identifying and tracking perpetrators, and digital evidence. Challenges to law enforcement under Article 303 of the Criminal Code include the principles of legality and legal certainty, inter-institutional coordination, and rapid technological developments, which pose challenges for law enforcement. Another challenge faced in law enforcement is the weak deterrent effect of criminal sanctions imposed on gambling perpetrators.